Corneal injury: Clinical and molecular aspects. (September 2019) - Barrientez, Brayden; Nicholas, Sarah E.; Whelchel, Amy; Sharif, Rabab; Hjortdal, Jesper; Karamichos, Dimitrios
Abstract: Currently, over 10 million people worldwide are affected by corneal blindness. Corneal trauma and disease can cause irreversible distortions to the normal structure and physiology of the cornea often leading to corneal transplantation. However, donors are in short supply and risk of rejection is an ever-present concern. Although significant progress has been made in recent years, the wound healing cascade remains complex and not fully understood. Tissue engineering and regenerative medicine are currently at the apex of investigation in the pursuit of novel corneal therapeutics. This review uniquely integrates the clinical and cellular aspects of both corneal trauma and disease and provides a comprehensive view of the most recent findings and potential therapeutics aimed at restoring corneal homeostasis. Highlights: Cornea trauma and disease can cause irreversible vision distortions. Clinical and molecular aspects of cornea trauma and disease are discussed. Recent findings and therapeutic options are outlined.